Sustainable nano-interventions to enhance crop yield, anthocyanin content, and marketability of onion (Allium cepa) - Jangir, Himanshi; Kaler, Brijesh; Srivastava, Gaurav; Das, Mainak (Frontiers in Nanotechnology, 2023)
Introduction: Agriculture predominantly follows three farming systems: natural, organic (organic manures for soil nutrition), and agrochemical intensive. Agrochemical-intensive farming uses synthetic fertilizers, insecticides, pesticides, and weedicides. It holds the most prominent place in the modern agriculture business. Humankind realizes that over-reliance on synthetic agrochemicals has resulted in the declining health of the ecosystem’s soil, water, and living species. It must explore strategies to reduce synthetic agrochemicals without compromising agricultural production to restore the ecological balance. Nano-formulations help lower dosages of agrochemicals, leading to the emergence of nano-agriculture. However, the critical challenge is how we could exploit nanomaterials’ power to selectively improve crop plants’ metabolic performance so that it has a better competitive edge in the field to withstand the nutrient-seeking pressure exerted by other plants. Methods: Here we have achieved the same by root treatment of the onion crop and then growing them in the presence of organic goat manure. Results: In a 2 years field trial with onion crops, we report an increase in yield through root treatment with nano-pyrite (FeS2) plus soil application of goat dropping (Test) as compared to the use of goat dropping alone (Control). In the first-year field trial (November 2018- April 2019), the total biomass (bulb + leaf) weight of the test sample was 4.75 kg (n = 86), while control samples weighed 3.5 kg (n = 83). The total bulb weight for the control and test was 2.6 and 3.6 kg, respectively. In the second-year field trial (December 2019- April 2020), the total biomass of the test sample was 2.65 kg (n = 64), while control samples weighed 2.30 kg (n = 64). We observed a yield-boosting effect of root treatment with nano-pyrite plus soil application of goat dropping in onion crops. As monitored by spectroscopic absorbance, there is a significant increase in the anthocyanin content in test bulbs (0.069) compared to control bulbs (0.02). Similarly, the relative flavanol content in test leaves (0.253) was significantly higher compared to the control samples (0.086). We have integrated nano-agriculture and organic farming, resulting in a hybrid form; nano-organic farming bolsters the metabolic fitness of the onion (Allium cepa) to achieve sustainable food production.